EXAMINING OPTIMAL CONTROL THROUGH THE APPLICATION OF (LQR) AND (LQT) APPROACHES IN THE CONTEXT OF DC MOTORS - admin journal; Lugas Jagad Satrianata; Laili Agustin Widyaningrum; Rahmania Ferdiansyah; Muhammad Hammam Raihan; Anggara Trisna Nugraha (Pusat Penelitian dan Pengabdian Masyarakat (P3M) - PPNS, 2023)
Different sectors of industry have a need for DC motors due to their benefits, such as substantial torque, absence of reactive power loss, no disruption to power supply, and precise control. Automation in control plays a crucial role in advancing science and technology. An effective control system must fulfill specified criteria, encompassing performance indices associated with accuracy, stability, and rapid response. An optimal control system is one fashioned through the optimization of performance indices, considered optimal when parameter values are chosen to maximize or minimize the selected performance index. In the context of DC motors. In the context of speed regulation using the Linear Quadratic Regulator optimal control technique, the optimization of performance indices involves configuring the Q matrix value. This, in turn, results in the generation of the K feedback amplifier matrix and the optimal L tracking matrix for the DC motor. The process is repeated for speed regulation in the DC motor using the Linear Quadratic Regulator optimal control technique, where performance index optimization is achieved by adjusting the Q matrix value, leading to the derivation of the K feedback amplifier matrix and the optimal L tracking matrix.